2021
DOI: 10.31083/j.ceog4804149
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective series of homologous intracytoplasmic sperm injection cycle results of 99 women with mosaic Turner syndrome

Abstract: Background: Although pregnancy is reported in both classical and mosaic forms of Turner syndrome (TS), both spontaneous and invitro-fertilisation (IVF) success rates were found higher in mosaic cases. In this study we analysed homologous intracytoplasmic sperm injection cycle results of infertile patients diagnosed with mosaic TS. Methods: Ninety nine female patients who had infertility complaints for 2 years or more and were diagnosed with mosaic TS were included in the study. They were treated according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition to ICSI or IVF, four out of 10 studies incorporated preimplantation genetic testing (PGT). Numerous investigations have used PGT to enhance reproductive outcomes, by selecting euploid embryos for transfer, with the aim of optimizing live birth rates, while minimizing the incidence of miscarriages and congenital abnormalities ( Giles et al , 2020 ; Gungor et al , 2021 ; Liao et al , 2021 ; Acet et al , 2022 ). PGT was performed at different phases of embryogenesis: biopsy of polar body ( Manno et al , 2009 ), Day 3 ( Giles et al , 2020 ) or Day 5 ( Liao et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to ICSI or IVF, four out of 10 studies incorporated preimplantation genetic testing (PGT). Numerous investigations have used PGT to enhance reproductive outcomes, by selecting euploid embryos for transfer, with the aim of optimizing live birth rates, while minimizing the incidence of miscarriages and congenital abnormalities ( Giles et al , 2020 ; Gungor et al , 2021 ; Liao et al , 2021 ; Acet et al , 2022 ). PGT was performed at different phases of embryogenesis: biopsy of polar body ( Manno et al , 2009 ), Day 3 ( Giles et al , 2020 ) or Day 5 ( Liao et al , 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, pregnancy rates were not different. Furthermore, the study by Gungor et al (2021) presented a cohort of 53 women with TS and ICSI-PGT versus 46 women with TS and ICSI-non-PGT and found significantly more pregnancies (36% vs 26%) and fewer miscarriages (11% vs 15%) per women after ICSI-PGT, respectively. Similar results after ICSI-PGT were found by Giles et al (2020) and Liao et al (2021) , who reported clinical pregnancy rates of 42–72% and miscarriage rates of 14–31%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations